Advances in Nanoengineered Terahertz Technology: Generation, Modulation, and Bio-Applications - Zhongwei Jin; Jing Lou; Fangzhou Shu; Zhi Hong; Cheng-Wei Qiu (Research)
Recent advancements in nanotechnology have revolutionized terahertz (THz) technology. By enabling the creation of compact, efficient devices through nanoscale structures, such as nano-thick heterostructures, metasurfaces, and hybrid systems, these innovations offer unprecedented control over THz wave generation and modulation. This has led to substantial enhancements in THz spectroscopy, imaging, and especially bio-applications, providing higher resolution and sensitivity. This review comprehensively examines the latest advancements in nanoengineered THz technology, beginning with state-of-the-art THz generation methods based on heterostructures, metasurfaces, and hybrid systems, followed by THz modulation techniques, including both homogeneous and individual modulation. Subsequently, it explores bio-applications such as novel biosensing and biofunction techniques. Finally, it summarizes findings and reflects on future trends and challenges in the field. Each section focuses on the physical mechanisms, structural designs, and performances, aiming to provide a thorough understanding of the advancements and potential of this rapidly evolving technology domain. This review aims to provide insights into the creation of next-generation nanoscale THz devices and applications while establishing a comprehensive foundation for addressing key issues that limit the full implementation of these promising technologies in real-world scenarios.